Spatial and Temporal Differentiation of Landscape Ecological Risk in Qinling-Daba Mountains - Chen Quantong; Yin Haoran; Li Yanhong; Dong Qingdong; Zhang Pingping; Zhu Lianqi (Shuitu baochi tongbao)
[Objective] The landscape ecological risk of the Qinling-Daba Mountains was scientifically assessed in order to provide a scientific basis for ecological security construction and for sustainable development in the region. [Methods] The spatial analysis method and the topographic distribution index method were used with land surface cover data for the Qinling-Daba Mountains from 2000 to 2020 to quantitatively analyze the temporal and spatial characteristics of the Qinling-Daba Mountains landscape ecological risk, and its dynamic changes on geographical terrain gradients. [Results] ① The overall ecological risk of the Qinling-Daba Mountains landscape was low, with significant spatial differences. There was an obvious spatial agglomeration effect, presenting a spatial distribution pattern of east and west sides, high in the middle, and low in the north and south. ② From 2000 to 2020, the ecological risk of the Qinling-Daba Mountains landscapes showed a downward trend, with low ecological risk areas expanding significantly, and high ecological risk areas shrinking significantly. ③ High ecological risk values were mostly concentrated in areas with high altitude, complex terrain, or low altitude and flat terrain. Low ecological risk values were predominantly located in areas with medium terrain gradients. [Conclusion] The overall landscape ecological risk in the Qinling-Daba Mountains showed a downward trend, indicating that the quality of the ecological environment in the region had improved. The distribution pattern of landscape ecological risk in the Qinling-Daba Mountains was greatly affected by topography and was relatively stable.